Preparation method of hollow amorphous N-TiO2 with photocatalytic high-concentration Cr (VI)
By constructing a hollow amorphous N-TiO2 shell on a three-dimensional Fe3O4 microsphere structure, the problem of low efficiency of existing photocatalysts when treating high-concentration pollutants is solved, and efficient photocatalytic degradation of high-concentration Cr(VI) is achieved, and the potential for industrial-grade wastewater treatment is available.
Patent Information
- Application Number
- CN202411737716.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing photocatalysts are inefficient in treating high concentrations of pollutants, especially in industrial-grade environments.
Using hollow amorphous N-TiO2 as a photocatalyst, a uniform amorphous single-doped shell is constructed on the three-dimensional Fe3O4 microsphere structure to improve the treatment capacity of high-concentration pollutants.
It realizes high-efficiency photocatalytic degradation of high concentration Cr(VI), improves carrier separation and transmission efficiency, and has the prospect of industrial-grade wastewater treatment.
Smart Images

Figure CN119565608A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalyst technology, and more specifically to a hollow amorphous N-TiO2 with high concentration of Cr(VI) in photocatalysis. 2 Preparation method Background Art
[0002] TiO 2 It is widely used in photocatalysts. Taking the doping of heteroatoms in photocatalysts as an example, oxygen vacancies caused by doping of metal elements such as Mn, C atoms doped into TiO 2 After the lattice forms Ti 3+ or oxygen vacancies, and N atoms are introduced into TiO 2 The lattice gaps generate abundant oxygen vacancies, and the introduction of impurity atoms induces beneficial defects that increase the separation rate of bulk carriers. However, in industrial-grade photocatalytic environments, single-atom-doped photocatalysts still have the problem of low efficiency in treating high-concentration pollutants.
[0003] At present, the separation and transfer speed of intrinsic carriers inside photocatalysts can be enhanced through appropriate morphology design. The structure of two-dimensional nanomaterials is conducive to shortening the diffusion path of photogenerated carriers and providing abundant active sites for adsorption and photocatalytic reactions. In practical applications, nanosheets tend to agglomerate in solution, making recycling complicated and increasing costs. The hollow structure of the three-dimensional microsphere matrix retains the thin shell characteristics of the sheet structure, and its internal cavity is larger, which enhances the actual light utilization rate.
[0004] Another way to improve the efficiency of carrier separation and transport is to construct amorphous components. For example, yellow amorphous TiO 2 Surface adsorption and photoactivity can be shown under visible light irradiation. Due to the change of electronic properties, amorphous TiO 2 The introduction of impurity atoms such as carbon and sulfur into the bulk phase exhibits higher photocatalytic activity. Summary of the invention
[0005] The purpose of the present invention is to provide a hollow amorphous N-TiO with high concentration of photocatalytic Cr(VI) 2 The preparation method constructs a uniform amorphous single-doped shell layer on the basis of a hollow structure to improve the treatment of high-concentration pollutants.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method comprises the following steps:
[0008] Step 1: After weighing ferric chloride hexahydrate, urea and tetrabutylammonium bromide in a molar ratio of 1:20:4, dissolve them in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195°C for 40 minutes to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 hours at a calcination temperature of 500°C; after the calcined product is cooled, grind it to obtain a three-dimensional Fe 3 O 4 Microspheres;
[0009] Step 2: Take the three-dimensional Fe prepared in step 1 3 O 4 0.3-0.8 g of microspheres were added to 35-70 mL of ethanol solution to prepare solution A, solution A was placed in an ice bath for 10 min, 0.10-0.55 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 10 mL of ethanol solution and mixed evenly to prepare solution B, solution B was added dropwise to solution A, the mixed solution was transferred to an ultrasonic cleaner, ultrasonicated for 30-90 min, the ultrasonic power was 40 kHz, and then the mixed solution was transferred to a water bath preheated at 60-100 ° C to react for 2-6 h to obtain Fe 3 O 4 / amorphous TiO 2 ;
[0010] Step 3: Take 0.3g of Fe prepared in step 2 3 O 4 / amorphous TiO 2 and 0.4-2.0g urea were added to 35-65mL ethanol solution and mixed evenly. The mixture was sealed in a 100mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 140-200℃ for 10h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain Fe 3 O 4 / Amorphous N-doped TiO 2 ;
[0011] Step 4: Fe prepared in step 3 3 O 4 / Amorphous N-doped TiO 2 After soaking in a low concentration acid solution for 30 min, the supernatant was collected and washed with deionized water until neutral, obtaining a hollow amorphous N-TiO with a high concentration of photocatalytic Cr(VI). 2 ;
[0012] The prepared hollow amorphous N-TiO 2 The physical and chemical properties are as follows: particle size is 1.2-1.5μm, shell thickness is 8.2-23.0nm; visible light transmittance is 42-70%; specific surface area is 63.3-182.95m 2 / g; photocurrent signal is 0.075-0.231μA / cm 2 ; The interface resistance is 374.8-943.2Ω; The oxygen vacancy signal is 0.08-0.38au.
[0013] Preferably, the ethylene glycol in step 1 is analytically pure, and its mass percentage concentration is ≥98%.
[0014] Preferably, the ethanol solution in step 2 and step 3 is analytically pure, and its mass percentage concentration is 99.5%.
[0015] Preferably, the mass percentage concentration of di(2-hydroxypropionic acid) diammonium dihydroxide titanium in step 2 is 50%, and the model is 65104-06-5.
[0016] Preferably, the low concentration acid solution in step 4 is hydrochloric acid with a concentration of 2-5 mol / L.
[0017] The method described in the present invention is based on three-dimensional Fe 3 O 4 As the structural framework, after ultrasonic mixing with di(2-hydroxypropionic acid) diammonium dihydroxide titanium as a titanium source, it can be hydrolyzed into Fe at low temperature. 3 O 4 / amorphous TiO 2 ; After reacting in an ethylene glycol solution mixed with urea and treated with a low concentration acid solution, a hollow amorphous N-TiO 2 Photocatalyst. The content of di(2-hydroxypropionic acid) diammonium dihydroxide titanium is the main reason for the difference in shell thickness, and low crystallization kinetics is the key to the generation and stability of amorphous materials. The test results show that the hollow amorphous N-TiO prepared by the present invention 2 Its structure exhibits typical amorphous properties: excellent photocurrent signal, low interface resistance and strong oxygen vacancy signal, which enable the photocatalyst to degrade Cr(VI)-containing wastewater with a concentration of 0.274 g / L under visible light irradiation.
[0018] The hollow amorphous N-TiO prepared by the present invention 2 The thickness can be controlled by the addition amount of di(2-hydroxypropionic acid) diammonium dihydroxide titanium, so that the prepared catalyst has the advantages of excellent visible light absorption rate, high carrier separation performance, etc., and has the prospect of being applied to industrial-grade wastewater treatment.
[0019] The hollow amorphous N-TiO prepared by the present invention 2 The stability of composition and structure enables the material to exhibit excellent reusability during use.
[0020] The raw materials of the method of the present invention are low in price, which effectively reduces the actual production cost of the materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanned structural diagram of the hollow amorphous material prepared by the present invention;
[0022] Figure 2 This is a transmission structure diagram of the hollow amorphous material prepared by the present invention;
[0023] Figure 3 The XRD diagram of the hollow amorphous material prepared in the present invention;
[0024] Figure 4 This is a diagram of the specific surface area of the hollow amorphous material prepared in the present invention;
[0025] Figure 5 This is a photocatalytic performance diagram of the hollow amorphous material prepared by the present invention;
[0026] Figure 6 This is a photocatalytic cycle performance diagram of the hollow amorphous material prepared by the present invention;
[0027] Figure 7 The present invention discloses the carrier separation activity of the hollow amorphous material. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0029] Example 1
[0030] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method comprises the following steps:
[0031] Step 1: Dissolve 4.4 mmoL of ferric chloride hexahydrate, 88 mmoL of urea and 17.6 mmoL of tetrabutylammonium bromide in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195°C for 40 min to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 h at a calcination temperature of 500°C; after the calcined product is cooled, grind it to obtain a three-dimensional Fe 3 O 4 Microspheres;
[0032] Step 2: Take the three-dimensional Fe prepared in step 1 3 O 40.3 g of microspheres were added to 35 mL of ethanol solution to prepare solution A, and solution A was placed in an ice bath for 10 min. 0.25 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 10 mL of ethanol solution and mixed evenly to prepare solution B. Solution B was added dropwise to solution A, and the mixture was transferred to an ultrasonic cleaner and ultrasonicated for 30 min at an ultrasonic power of 40 kHz. The mixture was then transferred to a water bath preheated at 80 °C and reacted for 2 h to obtain Fe 3 O 4 / amorphous TiO 2 ;
[0033] Step 3: Take 0.3g of Fe prepared in step 2 3 O 4 / amorphous TiO 2 and 1.2 g urea were added to 35 mL ethanol solution and mixed evenly. The mixture was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 160 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain Fe 3 O 4 / Amorphous N-doped TiO 2 ;
[0034] Step 4: Fe prepared in step 3 3 O 4 / Amorphous N-doped TiO 2 After soaking in a low concentration acid solution for 30 min, the supernatant was collected and washed with deionized water until neutral, obtaining a hollow amorphous N-TiO with a high concentration of photocatalytic Cr(VI). 2 ;
[0035] The prepared hollow amorphous N-TiO 2 The physical and chemical properties are as follows: particle size is 1.5μm, shell thickness is 10.5nm; visible light transmittance is 70%; specific surface area is 182.95m 2 / g; the photocurrent signal is 0.231μA / cm 2 ; The interface resistance is 374.8Ω; The oxygen vacancy signal is 0.38au.
[0036] Example 2
[0037] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method is the same as that in Example 1, except that in step 2, 0.10 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium complex is added to 10 mL of ethanol solution and mixed evenly to prepare solution B.
[0038] Example 3
[0039] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method is the same as that in Example 1, except that in step 2, 0.40 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium complex is added to 10 mL of ethanol solution and mixed evenly to prepare solution B.
[0040] Example 4
[0041] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method is the same as that in Example 1, except that in step 2, 0.55 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium complex is added to 10 mL of ethanol solution and mixed evenly to prepare solution B.
[0042] Example 5
[0043] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method comprises the following steps:
[0044] Step 1: Dissolve 4.4 mmoL of ferric chloride hexahydrate, 88 mmoL of urea and 17.6 mmoL of tetrabutylammonium bromide in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195°C for 40 min to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 h at a calcination temperature of 500°C; after the calcined product is cooled, grind it to obtain a three-dimensional Fe 3 O 4 Microspheres;
[0045] Step 2: Take the three-dimensional Fe prepared in step 1 3 O 4 0.8 g of microspheres were added to 70 mL of ethanol solution to prepare solution A, solution A was placed in an ice bath for 10 min, 0.25 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 10 mL of ethanol solution and mixed evenly to prepare solution B, solution B was added dropwise to solution A, the mixture was transferred to an ultrasonic cleaner, ultrasonicated for 30 min at an ultrasonic power of 40 kHz, and then the mixture was transferred to a water bath preheated at 80 ° C for 2 h to prepare Fe 3 O 4 / amorphous TiO 2 ;
[0046] Step 3: Take 0.3g of Fe prepared in step 2 3 O 4 / amorphous TiO 2and 1.2 g urea were added to 65 mL ethanol solution and mixed evenly. The mixture was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 160 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain Fe 3 O 4 / Amorphous N-doped TiO 2 ;
[0047] Step 4: Fe prepared in step 3 3 O 4 / Amorphous N-doped TiO 2 After soaking in a low concentration acid solution for 30 min, the supernatant was collected and washed with deionized water until neutral, obtaining a hollow amorphous N-TiO with a high concentration of photocatalytic Cr(VI). 2 ;
[0048] The prepared hollow amorphous N-TiO 2 The physical and chemical properties are as follows: particle size is 1.2μm, shell thickness is 8.2nm; visible light transmittance is 65%; specific surface area is 122.6m 2 / g; the photocurrent signal is 0.101μA / cm 2 ; The interface resistance is 778.5Ω; The oxygen vacancy signal is 0.18au.
[0049] Example 6
[0050] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method comprises the following steps:
[0051] Step 1: Dissolve 4.4 mmoL of ferric chloride hexahydrate, 88 mmoL of urea and 17.6 mmoL of tetrabutylammonium bromide in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195°C for 40 min to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 h at a calcination temperature of 500°C; after the calcined product is cooled, grind it to obtain a three-dimensional Fe 3 O 4 Microspheres;
[0052] Step 2: Take the three-dimensional Fe prepared in step 1 3 O 40.3 g of microspheres were added to 45 mL of ethanol solution to prepare solution A, solution A was placed in an ice bath for 10 min, 0.55 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 10 mL of ethanol solution and mixed evenly to prepare solution B, solution B was added dropwise to solution A, the mixture was transferred to an ultrasonic cleaner, ultrasonicated for 90 min at an ultrasonic power of 40 kHz, and then the mixture was transferred to a water bath preheated at 60 ° C for 6 h to prepare Fe 3 O 4 / amorphous TiO 2 ;
[0053] Step 3: Take 0.3g of Fe prepared in step 2 3 O 4 / amorphous TiO 2 and 2.0 g urea were added to 65 mL ethanol solution and mixed evenly. The mixture was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 140 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain Fe 3 O 4 / Amorphous N-doped TiO 2 ;
[0054] Step 4: Fe prepared in step 3 3 O 4 / Amorphous N-doped TiO 2 After soaking in a low concentration acid solution for 90 min, the supernatant was collected and washed with deionized water until neutral, obtaining a hollow amorphous N-TiO with a high concentration of photocatalytic Cr(VI). 2 ;
[0055] The prepared hollow amorphous N-TiO 2 The physical and chemical properties are as follows: particle size is 1.2 μm, shell thickness is 23.0 nm; visible light transmittance is 42%; specific surface area is 98.3 m 2 / g; the photocurrent signal is 0.129μA / cm 2 ; The interface resistance is 654.9Ω; The oxygen vacancy signal is 0.13au.
[0056] Example 7
[0057] A hollow amorphous N-TiO with high concentration of Cr(VI) for photocatalysis 2 The preparation method comprises the following steps:
[0058] Step 1: Dissolve 4.4 mmoL of ferric chloride hexahydrate, 88 mmoL of urea and 17.6 mmoL of tetrabutylammonium bromide in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195°C for 40 min to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 h at a calcination temperature of 500°C; after the calcined product is cooled, grind it to obtain a three-dimensional Fe 3 O 4 Microspheres;
[0059] Step 2: Take the three-dimensional Fe prepared in step 1 3 O 4 0.3 g of microspheres were added to 70 mL of ethanol solution to prepare solution A, solution A was placed in an ice bath for 10 min, 0.10 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 10 mL of ethanol solution and mixed evenly to prepare solution B, solution B was added dropwise to solution A, the mixture was transferred to an ultrasonic cleaner, ultrasonicated for 30 min at an ultrasonic power of 40 kHz, and then the mixture was transferred to a water bath preheated at 100 ° C to react for 2-6 h to obtain Fe 3 O 4 / amorphous TiO 2 ;
[0060] Step 3: Take 0.3g of Fe prepared in step 2 3 O 4 / amorphous TiO 2 and 0.4 g urea were added to 65 mL ethanol solution and mixed evenly. The mixture was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 200 °C for 10 h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain Fe 3 O 4 / Amorphous N-doped TiO 2 ;
[0061] Step 4: Fe prepared in step 3 3 O 4 / Amorphous N-doped TiO 2 After soaking in a low concentration acid solution for 30 min, the supernatant was collected and washed with deionized water until neutral, obtaining a hollow amorphous N-TiO with a high concentration of photocatalytic Cr(VI). 2 ;
[0062] The prepared hollow amorphous N-TiO 2 The physical and chemical properties are as follows: particle size is 1.3 μm, shell thickness is 12.8 nm; visible light transmittance is 56%; specific surface area is 63.3 m 2 / g; the photocurrent signal is 0.075μA / cm 2; The interface resistance is 943.2Ω; The oxygen vacancy signal is 0.08au.
[0063] In the above embodiment, the ethylene glycol in step 1 is analytically pure, and its mass percentage concentration is ≥98%. The ethanol solution in step 2 and step 3 is analytically pure, and its mass percentage concentration is 99.5%. The mass percentage concentration of di(2-hydroxypropionic acid) diammonium dihydroxide titanium in step 2 is 50%, and the model is 65104-06-5. The low-concentration acid solution in step 4 is hydrochloric acid with a concentration of 2-5 mol / L.
[0064] Comparative Example 1
[0065] 0.10 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 35 mL of ethanol solution, and the mixed solution was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 160 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain TiO 2 .
[0066] 0.55 mL of di(2-hydroxypropionic acid) diammonium dihydroxide titanium was added to 70 mL of ethanol solution, and 1.2 g of urea was added. The mixed solution was sealed in a 100 mL polytetrafluoroethylene-lined autoclave and hydrothermally treated at 160 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain AN-TiO 2 .
[0067] The hollow amorphous N-TiO prepared in Example 1 2 Named AH 2 -NTO. The hollow amorphous N-TiO prepared in Example 2 2 Named AH 1 -NTO. The hollow amorphous N-TiO prepared in Example 3 2 Named AH 3 -NTO. The hollow amorphous N-TiO prepared in Example 4 2 Named AH 4 -NTO.
[0068] The products prepared in Examples 1 to 4 and Comparative Example 1 were analyzed and described for their structural properties by means of microstructure diagrams, X-ray diffraction (XRD), specific surface area, photocatalytic performance, photocatalytic cycle performance and carrier separation activity.
[0069] 1. SEM image analysis
[0070] Figure 1 This is the scanning electron microscopy result of the product.
[0071] Figure 1a is the material before modification after low-temperature hydrothermal treatment and calcination - magnetite Fe 3 O 4 It exhibits an obvious flower-like structure. By combining it with diammonium titanium dihydroxide (2-hydroxypropionic acid), and controlling the hydrothermal conditions and the amount of diammonium titanium dihydroxide (2-hydroxypropionic acid), a hollow N-TiO with uniform shell thickness was synthesized. 2 Microspheres. Figure 1 b. Figure 1 As can be seen from the results of c, the surface size increases, but with the increase of the content of di(2-hydroxypropionic acid) diammonium dihydroxide titanium, the hollow N-TiO 2 The thickness is not uniform. Figure 1 As shown in b, the titanium source content is 0.25 mL, and the material synthesized after mechanical stirring for 30 min; even agglomeration occurs, such as Figure 1 As shown in c, the titanium source content is 0.55 mL and the material is synthesized after mechanical stirring for 30 minutes. Figure 1 df is a material synthesized under ultrasonic conditions. Its shell thickness ranges from Fe 3 O 4 35nm increased to AH 1 -NTO's 45nm, H 2 -NTO's 56nm and AH 4 In contrast, the surface layer of the photocatalyst synthesized under ultrasound was more uniform and the thickness variation was more regular, which indicated that the dispersion between the titanium source and the substrate was higher under ultrasound.
[0072] 2. Transmission electron microscopy analysis
[0073] Figure 2 The TEM image results in the figure confirm the formation of an amorphous hollow structure.
[0074] When adding Fe 3 O 4 In the case of particles, the product exhibits an obvious hollow structure, e.g. Figure 2 a. Figure 2 b. Figure 2 c. For example, as the content of di(2-hydroxypropionic acid) diammonium dihydroxide titanium increases, the brightness of the product in the TEM image decreases, indicating that the TiO 2 The increase in brightness and the presence of bubble-like structures in the HR-TEM image confirm that the material has an obvious hollow structure after etching. Figure 2 d. Figure 2 e. Figure 2 f. The HR-TEM image of the particles shows faint anatase lattice fringes, such as Figure 2g, which indicates that the ultrasound-assisted low-temperature process is beneficial for the amorphous TiO 2 The formation of TiO 2 When the morphology of the material changes from solid to uniformly hollow, the lattice fringes of the material disappear completely, and no lattice fringes are found in the local magnified image. Therefore, it is believed that the ultrasonic-assisted low-temperature process can reduce the crystallization kinetics of the material, thereby promoting the generation and stabilization of the amorphous structure.
[0075] 3. XRD pattern analysis
[0076] Figure 3 The XRD spectra in provide additional evidence for the amorphous nature and nitrogen doping of the material. Figure 3 The XRD characteristic peak results show that pure TiO 2 The particles present anatase crystal structure. The main characteristic diffraction peaks basically disappear after N doping, indicating that the product is a typical amorphous state. This is because the crystallization rate is low at low temperatures, resulting in the product not transforming into the corresponding crystal structure. The diffraction peaks of the product after the etching reaction remain consistent, indicating that the template is completely removed.
[0077] 4. Specific surface area analysis
[0078] Figure 4 The results showed that AH 2 -NTO and AN-TiO 2 The specific surface areas are 182.95 and 35.25 m 2 This result shows that the specific surface area of the hollow material increases, which will provide more adsorption sites for pollutants.
[0079] 5. Photocatalytic performance diagram analysis
[0080] In the visible light catalytic performance experiment, the light source used has a power of 200mW / cm 2 The light intensity was 300W xenon lamp. The photocatalysis of 100mg / L Cr(VI) wastewater with pH of 2.01 was taken as an example to illustrate the specific photocatalytic process. The whole process involves two stages: dark adsorption and photocatalysis. 40mg of photocatalyst was added to 40mL of 100mg / L Cr(VI) wastewater, and the real-time concentration of Cr(VI) under different illumination times was monitored by continuous sampling. After the dark adsorption was completed, the light source was turned on and visible light was continued for 2h to detect the degradation of Cr(VI). The real-time concentration of Cr(VI) was measured by diphenylcarbazide colorimetry. Figure 5 The photocatalytic performance results in a show that with the increase of illumination time, the concentration of Cr(VI) gradually decreases, proving that the photocatalytic activity of the material is improved. After 120 min of visible light irradiation, pure TiO 2 After deducting the amount removed by adsorption, pure TiO2 The photocatalytic efficiency of AN-TiO is close to zero. 2 The photocatalytic activity is higher than that of pure TiO 2 The increase was 79.78%, indicating that the production of amorphous structure significantly improved the actual catalytic efficiency of the material. 2 In comparison, AH 1 The catalytic concentration of -NTO increased to 63 mg / L, indicating that the formation of the hollow structure enhanced the photocatalytic activity of the material. Continuing to increase the content of the titanium source, the catalytic activity of the material will be further improved, AH 2 -NTO can completely photocatalyze 100mg / L.
[0081] The optimized photocatalyst has a significant effect on the treatment of high-concentration chromium-containing wastewater, especially with the assistance of triethanolamine. Figure 5 b. For example, 0.15 g / L Cr(VI) was completely removed within 120 min. In addition, the efficiency of photocatalytic removal of Cr(VI) was still very high. When the concentration of Cr(VI) was 0.2 g / L, 0.3 g / L and 0.5 g / L, the efficiency of photocatalytic removal of Cr(VI) was 97.27%, 89.93% and 54.3%, respectively. Obviously, the method synthesized in this patent has the potential to treat high-concentration chromium-containing wastewater.
[0082] 6. Analysis of photocatalytic cycle performance diagram
[0083] Figure 6 Shows the AH 2 -NTO photocatalyst cyclic activity study, Cr (VI) was photocatalyzed 5 times under the same conditions. Even after 5 cycles, AH 2 -NTO photocatalyst can still achieve nearly 100% Cr(VI) reduction efficiency, indicating that it has stable performance and good practical application prospects.
[0084] 7. Carrier separation activity analysis
[0085] Figure 7 The results of a show that the hollow structure of the product is conducive to light absorption. For example, under 500nm light, pure AN-TiO 2 The light transmittance of AH is about 8%, and after forming a hollow structure, its light transmittance increases to about 70%. 2 -NTO has a lower light transmittance than pure AN-TiO 2 , which shows that the production of hollow structure is conducive to the material's utilization of visible light.
[0086] Evidence for the high carrier separation efficiency comes from electron spin resonance, transient photocurrent response, and electrochemical impedance spectroscopy. Figure 7 b The results show that compared with pure TiO2 Compared with AN-TiO 2 An electron spin resonance signal is shown at g = 2.004, which may be due to the generation of oxygen vacancies inside the material. 2 -NTO's ESR signal is better than AH 1 -NTO has a signal about 3 times that of NTO, indicating that it has excellent carrier separation ability. Figure 7 c, AH 2 -NTO and AN-TiO 2 The photocurrent density is 0.229uA / cm 2 and 0.044uA / cm 2 The 5.2-fold increase indicates that the material can generate more photoelectrons per unit time under visible light irradiation. Figure 7 d shows the electron transfer from the photocatalyst to the external circuit resistor, where the arc radius increases in order from TiO 2 to AN-TiO 2 The results show that the generation of amorphous and nitrogen doping is beneficial to electron transfer. 2 In comparison, AH 2 The electrochemical impedance of -NTO is reduced by 2.5 times, which indicates that the hollow structure enhances the electron transfer efficiency and thus improves the photochemical quantum yield. Combined with the excellent photocatalytic activity of the material, we believe that the hollow amorphous N-doped TiO 2 The microspheres have excellent carrier separation efficiency.
[0087] The above are only preferred embodiments of the present invention. It should be noted that for those skilled in the art, other equivalent variations and improvements can be made under the technical enlightenment provided by the present invention, which should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing hollow amorphous N-TiO2 with photocatalytic high concentration of Cr(VI), characterized in that: The following steps are involved: Step 1: After weighing ferric chloride hexahydrate, urea and tetrabutylammonium bromide in a molar ratio of 1:20:4, dissolve them in a three-necked flask containing 180 mL of ethylene glycol solution to form a red solution, heat the solution and reflux at 195° C. for 40 min to form a green precipitate; calcine the green precipitate in a nitrogen-protected tubular furnace for 2 h at a calcination temperature of 500° C.; after the calcined product is cooled, grind it to obtain three-dimensional Fe3O4 microspheres; Step 2: Take 0.3-0.8 g of the three-dimensional Fe3O4 microspheres prepared in step 1 and add them to 35-70 mL of ethanol solution to prepare solution A. Ice-bath solution A for 10 min. Take 0.10-0.55 mL of di(2-hydroxypropionic acid) diammonium titanium dihydroxide and add them to 10 mL of ethanol solution and mix them evenly to prepare solution B. Add solution B dropwise to solution A. Transfer the mixture to an ultrasonic cleaner and perform ultrasonic cleaning for 30-90 min at an ultrasonic power of 40 kHz. Transfer the mixture to a water bath preheated at 60-100°C and react for 2-6 h to obtain Fe3O4 / amorphous TiO2. Step 3: Take 0.3g of Fe3O4 / amorphous TiO2 prepared in step 2 and 0.4-2.0g of urea, add them into 35-65mL of ethanol solution and mix them evenly. Seal the mixture in a 100mL polytetrafluoroethylene-lined autoclave, and perform hydrothermal treatment at 140-200°C for 10h. After the reaction is completed, centrifuge, wash and dry to obtain Fe3O4 / amorphous N-doped TiO2. Step 4: Soak the Fe3O4 / amorphous N-doped TiO2 prepared in step 3 in a low concentration acid solution for 30 minutes, collect the supernatant, and wash the supernatant with deionized water until it is neutral to obtain a hollow amorphous N-TiO2 with a photocatalytic high concentration of Cr(VI); The physical and chemical properties of the prepared hollow amorphous N-TiO2 are as follows: particle size is 1.2-1.5μm, shell thickness is 8.2-23.0nm; visible light transmittance is 42-70%; specific surface area is 63.3-182.95m 2 / g; photocurrent signal is 0.075-0.231μA / cm 2 ; The interface resistance is 374.8-943.2Ω; The oxygen vacancy signal is 0.08-0.38au.
2. The method for preparing hollow amorphous N-TiO2 with photocatalytic high concentration of Cr(VI) according to claim 1, characterized in that: The ethylene glycol in step 1 is analytically pure, and its mass percentage concentration is ≥98%.
3. The method for preparing hollow amorphous N-TiO2 with photocatalytic high concentration of Cr(VI) according to claim 1, characterized in that: The ethanol solution in step 2 and step 3 is analytically pure, and its mass percentage concentration is 99.5%.
4. The method for preparing hollow amorphous N-TiO2 with photocatalytic high concentration of Cr(VI) according to claim 1, characterized in that: The mass percentage concentration of di(2-hydroxypropionic acid) diammonium dihydroxide titanium in step 2 is 50%, and the model is 65104-06-5.
5. The method for preparing hollow amorphous N-TiO2 with photocatalytic high concentration of Cr(VI) according to claim 1, characterized in that: The low concentration acid solution in step 4 is hydrochloric acid with a concentration of 2-5 mol / L.
Citation Information
Patent Citations
Preparation method and application of TiO2 nanotube coated with amorphous layer
CN104098134A
Application of Fe3O4 / mTiO2 magnetic mesoporous nanometer material in degradation of pesticide
CN105478122A
Preparation method of iron ion doped titanium dioxide nano material
CN110327926A
Amorphous tio 2 material, preparation method therefor, and photocatalyst comprising same
WO2017200328A1